Bensulfuron-Methyl Treatment of Soil Affects the Infestation of Whitefly, Aphid, and Tobacco Mosaic Virus on Nicotiana tabacum - Li, Renyi; Islam, Saif Ul; Wu, Zujian; Ye, Xiujuan (Frontiers in Plant Science, 2016)
Bensulfuron-methyl (BSM) is widely used in paddy soil for weed control. BSM residue in the soil has been known to inhibit the growth of sensitive crop plants. However, it is unknown whether BSM residue can affect the agrosystem in general. In this study, we have found significant effects of BSM on the infestation of Bemisia tabaci, Myzus persicae and Tobacco mosaic virus (TMV) in Nicotina tabacum. The soil was treated with BSM before the pest inoculation. The herbicide-treated tobaccos showed resistance to B. tabaci, but this resistance could not be detected until 15-day post-infestation when smaller number of adults B. tabaci appeared. In M. persicae assay, the longevity of all development stages of insects, and the fecundity of insects were not significantly affected when feeding on BSM-treated plants. In TMV assay, the BSM treatment also reduced virus-induced lesions in early infection time. However, the titer of TMV in BSM treated plants increased greatly over time and was over 40-fold higher than the mock-infected control plants after 20 days. Further studies showed that BSM treatment increased both jasmonic acid (JA) and salicylic acid (SA) levels in tobacco, as well as the expression of target genes in the JA and SA signaling pathways, such as NtWIPK, NtPR1a and NtPAL. NtPR1a and NtPAL were initially suppressed after virus-inoculation, while NtRDR1 and NtRDR6, which play a key role in fighting virus infection, only showed up or were down-regulated 20 days post virus-inoculation. Taken together, our results suggested that BSM residue in the soil may affect the metabolism of important phytohormones such as JA and SA in sensitive plants and consequently affect the plant immune response against infections such as whitefly, aphids and viruses.